Grapho-Phonological Features in Qumashah Al-Ulayan2019;s Uyunu Qadhrah (Dirty Eyes) (Global Journal of Human-Social Science, 2020)
This paper examines the linguistics features of Qum shah al-ulay n s text Uy nu al-Qadhrah Dirty Eyes and how these linguistics features enhance meaning achievement The paper argues that stylistics is a bridge between literary criticism and linguistics This study therefore applies the insights and techniques of general linguistics to investigate the stylistic value of graphological and phonological devices as semantic signifiers in the text The study deploys M A K Halliday s Systemic Functional model as the analytical tool to examine the use of graphology such as punctuations and paragraphing Phonological devices like repetition alliteration and rhyme in the text are also examined The study posits that at level of language study graphological and phonological structure play a vital role in encoding the meaning and aesthetics of Qumash h al Ulay n s text